Conversations with Gert Biesta and Carl Anders Säfström (Praxis Educativa, 2018)
In the present article, we propose to talk with Gert Biesta and Carl Andres Säfström from a manifesto of their authorship on the position they have about the school in the contemporaneity. We point out some ideas that are at the base of the works that we develop and in the current of research to which we are affiliated –research with the daily ones–, that is, educational networks and conceptual characters. Then, we present some positions that we understand as differentiated from those defended by these authors: the relationships between practices and theories, the articulations between educational spaces and times and the idea that the processes of ‘teaching learning’ happen all the time, in a movement which includes the “still is not” in the negotiation between “what is” and what “is not yet”.
Keywords: cotidians; educational networks; educational spaces-times; learning-teaching processes; practicestheories